Antimicrobial Polymers in the Nano-World - Marta Álvarez-Paino; Alexandra Muñoz-Bonilla; Marta Fernández-García (Nanomaterials, 2017)
Infections are one of the main concerns of our era due to antibiotic-resistant infections and the increasing costs in the health-care sector. Within this context, antimicrobial polymers present a great alternative to combat these problems since their mechanisms of action differ from those of antibiotics. Therefore, the microorganisms’ resistance to these polymeric materials is avoided. Antimicrobial polymers are not only applied in the health-care sector, they are also used in many other areas. This review presents different strategies that combine nanoscience and nanotechnology in the polymer world to combat contaminations from bacteria, fungi or algae. It focuses on the most relevant areas of application of these materials, viz. health, food, agriculture, and textiles.